Pricing Mechanism of Palm Oil Transactions within the Framework of Sharia Economics: Conformity, Challenges, and Implications - Juhanadi, Andi Ismail; Nilfatri; Haeran; Fatimah, Siti (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to analyze the pricing practices and harvest deduction systems in the transactions of fresh fruit bunches (FFB) of oil palm at Ram Sido Mukti Jaya, Dendang Subdistrict, Tanjung Jabung Timur Regency, from the perspective of Islamic economics. Employing a qualitative descriptive method, data were collected through observation, semi-structured interviews, and literature review. The findings indicate that the prevailing transaction mechanisms do not fully reflect the principles of justice, transparency, and mutual consent as upheld in Islamic economic principles. The imbalance in farmers' bargaining positions, the absence of clear contractual agreements, and the lack of open information regarding prices and deductions are key indicators of inequality. These findings highlight the need for a thorough evaluation of transaction governance and the imperative to incorporate Islamic values into commodity trading practices. The implications of this study suggest that business actors should adopt Sharia-compliant principles in their transactions, that Islamic cooperatives should be strengthened to enhance farmers’ bargaining power, and that the findings may serve as a foundation for policymakers and researchers in formulating strategies for a fair, transparent, and socially as well as spiritually sustainable trade system